Improving the operation of an asymmetric inverter with magnetically coupled inductors for energy storage systems - Martynov, D. V.; Rudenko, Y. V.; Martynov, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Bidirectional DC-DC converters are widely used in energy storage systems for efficient energy transfer. One of the effective converters for such systems is the asymmetric inverter with a magnetically coupled inductors. To enhance the efficiency of this converter for energy storage applications, it is necessary to optimize its parameters. Objective. The objective is to develop a mathematical model of an asymmetric inverter with magnetically coupled inductors and based on this model, to establish the conditions for improving the energy efficiency of the inverter in energy storage systems. Methods. The study uses the state-space averaging method and simulation modelling to analyse operational processes. Results. Analytical expressions were derived for calculating current parameters of the magnetically coupled inductor within switching intervals. A correlation was identified between the inductor’s inductance and power source parameters under conditions that eliminate circulating currents, thus reducing static energy losses in the inverter. Novelty. Based on these expressions, new analytical and graphical dependencies were established, illustrating relationships between the inductor parameters and the magnetic coupling coefficient of its windings. These dependencies determine the boundaries of the discontinuous conduction mode for the asymmetric inverter with a magnetically coupled inductors within its switching range. Practical value. The application of these dependencies during the design phase allows for a reduction in both static and dynamic energy losses in the inverter using discontinuous conduction mode. This will also improve the dynamics of transient processes during changes in the direction of energy flow, which is a significant advantage in the development of hybrid power systems for electric vehicles.

В системах накопичення енергії широко використовуються перетворювачі постійної напруги в режимах двонаправленої передачі енергії. Одним з ефективних перетворювальних пристроїв для застосування в таких системах є асиметричний інвертор з магнітозв’язаними індуктороми. Для використання вказаного перетворювача в системах енергонакопичення необхідним є удосконалення його параметрів для підвищення ефективності перетворювача. Мета. Метою є розробка математичної моделі асиметричного інвертора з магнітозв’язаними індукторами та визначення на її основі умов підвищення енергетичної ефективності такого інвертора при застосуванні в системах накопичення енергії. Методи. При дослідженні процесів в роботі використано метод усереднення в просторі станів та методи імітаційного моделювання. Результати. Розроблено аналітичні вирази для розрахунків параметрів струмів магнітозв’язаних індукторів на інтервалах комутації, визначено взаємозв’язок між його індуктивністю та параметрами джерел електроживлення, при яких циркуляційні струми відсутні, що зменшує статичні втрати енергії інвертора. Новизна. На основі розроблених виразів отримано нові аналітичні та графічні залежності між параметрами індуктора та коефіцієнтом магнітного зв’язку між їх обмотками, що визначають межі області переривчастої роботи асиметричного інвертора з магнітозв’язаними індукторами в діапазоні його комутації. Практична значимість. Використання отриманих залежностей на етапі проектування дозволяє зменшити статичні та динамічні втрати енергії інвертора завдяки використанню режиму переривчастої провідності. Це також дозволить покращити динаміку перехідних процесів при зміни напрямку протікання електроенергії, що є суттєвою перевагою при створенні гібридних систем електроживлення електротранспортних засобів.
Keywords: energy storage systems; bidirectional DC-DC converter; asymmetric inverter; magnetic coupling inductors; circulating current; системи накопичення електроенергії; двонаправлений перетворювач постійної напруги; асиметричний інвертор; магнітозв'язані індуктори; циркулюючий струм